Contexto ambiental de los procesos de cambio de uso y cobertura del suelo en Calimaya, Altiplano Mexicano - Amorim Homem de Abreu Loureiro, Guilherme (2022)
The convergence of conventional agriculture, real estate investments and sand and gravel mining characterize Calimaya as one of the most negatively impacted municipalities of the Mexican altiplano by anthropic activities. The objective of this work was to analyse the geographical and environmental context of land use and land cover change (LULCC) processes in this Municipality. For this, the following indicators were estimated: the cover change rate proposed by Food and Agriculture Organization of the United Nations by using the land cover classes proposed by the Intergovernmental Panel on Climate Change. LULCC in the last decade (2010-2019) were: deforestation and advancement of potato crop in the Nevado de Toluca Flora and Fauna Protection Area; decrease in the process of occupation of cropland areas by settlements; and, soil degradation in abandoned mines.